Inhibition of CD45-specific phosphatase activity restores the differentiation potential of aged mesenchymal stromal cells: implications in regenerative medicine - Madhurima Das; Isha Behere; Ganesh Ingavle; Anuradha Vaidya; Vaijayanti Prakash Kale (Biological Research)
Abstract Background Aging affects the reparative potency of mesenchymal stem/stromal cells (MSCs) by diminishing their proliferation and differentiation capability; making them unsuitable for regenerative purposes. Earlier we showed that MSCs acquire the expression of CD45 as a consequence of aging, and this increased expression is associated with downregulated expression of osteogenic markers and upregulated expression of adipogenic and osteoclastogenic markers. However, whether CD45 is actively involved in the aging-mediated deregulated differentiation in the MSCs was not elucidated. Results In the present study, we showed that pharmacological inhibition of CD45-specific phosphatase activity in the aged MSCs restores their differentiation potential to young-like. Investigation of the molecular mechanism involved in the process showed that several regulatory kinases like p38, p44/42, Src, and GSK3β are in their dephosphorylated form in the aged MSCs, and importantly, this status gets reversed by the application of a CD45-specific PTP inhibitor. Conversely, pharmacological inhibition of these kinases in young MSCs imposes an aged-like gene expression profile on them. Additionally, we also showed that the secretome of aged MSCs affects the viability and differentiation of primary chondrocytes, and this detrimental effect is reversed by treating aged MSCs with the PTP inhibitor. Our data demonstrate that the aging-mediated expression of CD45 in MSCs alters their differentiation profile by dephosphorylating several kinases and treating the aged MSCs with a CD45 PTP activity inhibitor rejuvenates them. Conclusions CD45 can be used as an aging marker for mesenchymal stem cells. Alteration of CD45 phosphatase activity could have significant implications for the use of MSCs in regenerative medicine. Graphical abstract The rejuvenating effect of CD45-specific PTP inhibitor on aged MSCs: Aging diminishes the reparative potency of mesenchymal stem/stromal cells (MSCs) by increasing CD45 expression in them. This increased expression of CD45 leads to the downregulation of osteogenic and chondrogenic markers and upregulation of adipogenic and osteoclastogenic markers. Inhibition of CD45-specific phosphatase activity in aged MSCs restores their differentiation potential to young-like by restoring the phosphorylation status of various regulatory kinases (p38, p44/42, Src, and GSK3β). Elevated expression of osteoclastic markers in aged MSCs, also reversed after CD45-specific PTP inhibitor treatment. These findings suggest that targeting CD45 phosphatase activity could enhance the regenerative capabilities of aged MSCs, making them more suitable for therapeutic applications